Tarekat and Social Change: The Influence of Tarekat Movement in Sukamanah Rebellion, Against Japan in 1944 - Baihaqi, Ahmad Fauzan; Ramadhan, Fauzan Syahru; Rahardjo, Bahagio; Pratama, Olga S. (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
This paper discusses the influence of the tarekat movement in the rebellion against Japan in 1944 from the pesantren in Sukamanah, Tasikmalaya, West Java. After the treaty of Kalijati, 1942, Japan took full control of the land of West Java. Sociologically it was considered to drain and enslave the people of Sukamanah, and theologically coupled with the Seikerei ritual imposed by the Japanese and considered by the leader of Sukamanah, Zaenal Mustafa, as a form of violation of Islamic principles became the motivation for the rebellion. This paper uses the historical method with a social approach. This writing uses the point of view of Sartono Kartodirdjo's social-religious approach in seeing the symptoms of resistance to Colonialism based on religious elites and the impact of a significant social change due to the oppression of colonialism which here is Japanese Imperialism, Tarekat being the only base of resistance. The final finding is that Zaenal Mustafa's role as a figure who further developed Tarekat Syattariyah, although political resistance in Java was very dominant was closely related to the development of the Tarekat Qadiriyah wa Naqsabandiyah community into a new force of resistance in West Java.